Magnetically driven nanoparticles: 18FDG‐radiolabelling and positron emission tomography biodistribution study. (4th January 2017) - De Simone, Mariarosaria; Panetta, Daniele; Bramanti, Emilia; Giordano, Cristiana; Salvatici, Maria C.; Gherardini, Lisa; Menciassi, Arianna; Burchielli, Silvia; Cinti, Caterina; Salvadori, Piero A.
Abstract : Superparamagnetic iron oxide nanoparticles (SPIONs) have received increasing interest as contrast media in biomedical imaging and innovative therapeutic tools, in particular for loco‐regional ablative treatments and drug delivery. The future of therapeutic applications would strongly benefit from improving the capability of the nanostructured constructs to reach the selected target, in particular beyond the intravascular space. Besides the decoration of SPIONs surface with ad hoc bioactive molecules, external magnetic fields are in principle able to remotely influence SPIONs' physiological biodistribution and concentrate them to a specific anatomical region or portion of a tissue. The reduction of SPIONs administered to the body and the need for defining the effective SPIONs local concentration suggest that PET/CT may be a method to quantitatively detect the nanoparticles accumulation in vivo at low concentration and assess their tridimensional distribution in response to an external magnetic field and in relation to the local anatomy highlighted by CT imaging. Here, we report on the possibility to assess the spatial distribution of magnetically‐driven radiolabelled SPIONs in a peripheral tissue (mouse thigh) with microPET/CT imaging. To this aim we labelled SPIONs using 18 F‐2‐fluoro‐2‐deoxyglucose as a synthon, by chemoselective oxime formation between its open‐chain tautomer and nanoparticle amino‐groups, and employed microPET/CT imaging to measure the radiolabelled construct biodistribution in a small animal model, following intravenous administration, with and without the application of a permanent magnet onto the skin. The in vivo and ex vivo results showed that micro‐PET/CT was able to demonstrate the localizing action of the magnet on SPIONs and provide information, in a multimodal 3D data set, about SPIONs biodistribution taking into account the local anatomy. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : PET imaging demonstrates that, after systematic administration, magnetic nanoparticles can be locally concentarted to a specific anatomycal site with intact vascularity by an external static magnetic field.